Photocatalytic Oxidation of Carbofuran Pesticide Using Zinc Oxide - Fadaei, A.M.; Mohammadi Moghadam, F. (Asian Journal of Chemistry, 2014)
In recent years, the application of ultraviolet irradiation and zinc oxide (UV/ZnO) process water and wastewater treatment has gained removal activity of the persistence organic compounds. The degradation of carbofuran pesticide was investigated under ultraviolet irradiation and zinc oxide (UV/ZnO) process. Likewise, the effect of the operational parameters such as reaction volume, initial concentration of catalyst, initial carbofuran concentration, light intensity and pH were studied. In this study the (UV/ZnO) process at different initial concentrations (50-250 mg/L), 5 different initial pH and 5 different initial concentration of catalyst was investigated. Analyses were performed by gas chromatography mass spectroscopy. Results showed that the carbofuran initial concentration of 50 mg/L, ZnO concentration of 300 mg/L, pH of 8, light intensity of 125 watts and reaction volume of 150 mL, were the optimum condition for degradation of carbofuran by UV /ZnO system. This study demonstrated that carbofuran could be effectively degraded by ultrasonic irradiation.